Levels of selected metals in spices cultivated in Southwest Ethiopia: Occurrence and health risk assessment - Gemechu, Tura; Legesse, Abi; Chandravanshi, Bhagwan Singh; Megersa, Negussie (European Journal of Chemistry, 2025)
In this study, the levels of seven metals (Ca, Cd, Cr, Cu, Zn, Pb, and Ni) in the soil and spice plants grown around Oromia Region of Southwest Ethiopia were analyzed using flame atomic absorption spectrometry (FAAS) after acid digestion. The pH of the soil samples was found to be in the range of 5.86 to 6.57, with organic matter 13.93 to 20.59% and electrical conductivity 0.28 to 0.49 mS/m. Among the metals determined, Ca was the most prevalent, ranging from 429.01 to 5369.67 mg/kg, Zn 31.88 to 67.70 mg/kg and Cu 7.62 to 10.67 mg/kg in plants, while Cd, Cr, Pb, and Ni were not detected in the spice plants. Ca was the most abundant metal in soils, ranged from 1195.67 to 4147.17 mg/kg, followed by Zn, Cr, Ni, and Cu, ranging from 112.90 to 120.25 mg/kg, 21.92 to 45.76 mg/kg, 21.40 to 56.93 mg/kg and 13.03 to 28.67 mg/kg, respectively. Cd and Pb were not detected in the soil samples. The hazard quotient and hazard index values of Cu and Zn in all spices were below one, which may ensure that these spices do not pose substantial health risks to consumers.